Strategi Komunikasi Yang Mendukung Perkembangan Pariwisata Berbasis Ekonomi Kerakyatan - Setyowati, Retno Manuhoro (Jurnal The Messenger, 2016)
This research was emerged by Centra Java Government policy which placed tourism sector as the second key sectors beside agriculture and industries. A kind of tourism force is by ecotourism wich environmentally responsible travel and visits to relatively undisturbed natural areas, in order to enjoy and appreciate nature and any accompanying cultural features, both past and present, that promote conservation, has low visitor impact, and provides for beneficially active socio-economic involvement of local population. Then, the strategic communication choose Participatory Rural Appraisal (PRA) to increase them. PRA is a participatory approach, new innovation method for improving efficacy and rapidity in data collection. Participatory method was interested the community in prepare the action program and developing the learning process forsolving the environment problems. Leading by Pamong Budaya as opinion leader, this strategic communication is a way tocreate an effective communication and automatically help rural community to increase their live by ecotourism.